Religious Inclusiveness in Schools: An Integrative Exploration of Educational Realities in Radicalism Red Zone Areas - Muthi'ah, Anisatun; Zuhriyah, Lailatuzz; Widyasanti, Nisa Setya; Marzuki, Ismail; Emawati, Emawati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The issue of religious radicalism, both in opinion and action, remains a common challenge in Indonesia. This phenomenon is not only prevalent in society but also extends to educational institutions, including schools. Religious inclusivity is a key to understanding and overcoming this issue. This study aims to explore the level of religious inclusivity among students, teachers, and educational staff, as well as to document the implementation of inclusivity principles in school activities and learning environments in red-zone schools, one of which is in Cirebon. The method employed is a mixed-methods approach involving 155 participants, including students, teachers, and educational staff. This approach combines a verified questionnaire, based on expert judgment, to obtain quantitative data, with observations, interviews, and documentation to collect qualitative data. The research findings indicate that these results can serve as a reference for mapping issues as an initial step in developing a school model that integrates religious inclusivity into every program and learning environment, thereby minimizing the potential for radicalism. The novelty of this research lies in the comprehensive mapping of the level of religious inclusivity in schools in red zones of radicalism, which has rarely been revealed before, while also offering a conceptual framework that can be adapted to the educational context in other areas prone to radicalism.